The Form of Language Choice on Deddy Corbuzier’s Youtube Podcast - Amirin, Amirin; Mardikantoro, Hari Bakti; Yuniawan, Tommi (Universitas Negeri Semarang, 2021)
One of the most interesting youtube contents in Indonesia goes to Deddy Corbuzier’s youtube podcast. It is caused by the various guests who are invited and the use of several languages in the podcast when they are doing interaction each other. As a youtuber who masters more than two languages, Deddy Corbuzier has to take an action of language choice in order to the interaction in the podcast flows smoothly. The aim of this research is to describe the form of language choice on Deddy Corbuzier’s youtube podcast. The data collection is done using observation method with observe-involve-free-statement and taking notes techniques. After the data is collected then they are analyzed using determining elements choice technique. Hereinafter, the data is presented using informal method or using words. The results of this research are 1) the form of singular variety language in using formal and informal Indonesian language, 2) the form of code-switching from Indonesian language to foreign language and vice versa, 3) the form of code mixing in words, phrases, idioms, and clauses insertion from foreign language to Indonesian language.